Cervical cancer in pregnancy: Analysis of the literature and innovative approaches. Issue 9 (20th February 2019) - Perrone, Anna Myriam; Bovicelli, Alessandro; D'Andrilli, Giuseppina; Borghese, Giulia; Giordano, Antonio; De Iaco, Pierandrea
Abstract: Cervical cancer is one of the most common gynecological malignancies diagnosed during pregnancy although, fortunately, it is a rare event. In majority of cases, the management of cervical cancer in pregnant women is not different from nonpregnant women and prognosis seems not compromised by pregnancy. The association between cancer and pregnancy appears to be a significant challenge for women and specialists and the decisions about therapy must be individualized and taken by a multidisciplinary team. This review is focused on cervical cancer in pregnancy. The aim is to discuss the diagnosis, potential biomarkers and molecular aspects, therapeutic approaches, and prognosis from intraepithelial cervical neoplasia to invasive cervical cancer (early and advanced stages) in different gestational ages. We provide an overview of the current literature regarding the treatment strategies of concurrent pregnancy and cervical cancer cases and we propose some clinical advices to help clinicians to manage this condition. A mention about the effects of the conservative therapy (as conization) on fertility, the human papillomavirus vaccine in pregnant women and our center's experience with obstetrical and oncological outcomes are reported. Abstract : Cervical cancer is one of the most common gynecological malignancies diagnosed during pregnancy. The association between cancer and pregnancy represents a significant challenge for women and specialists and the decisions about therapy must be individualized and taken in a multidisciplinary team. The aim of this review is to discuss the diagnosis, potential biomarkers and molecular aspects, therapeutic approaches, and prognosis from intraepithelial cervical neoplasia to invasive cervical cancer.